Developing the CARE intervention to enhance ethical self-efficacy in dementia care through the use of literary texts - Lauridsen, Sigurd; Schou-Juul, Frederik; Folker, Anna Paldam; Simonsen, Peter; Phil, Marie-Elisabeth; Skov, Sofie Smedegaard (BMC medical ethics, 2023)
Background Dementia care is essential to promote the well-being of patients but remains a difficult task prone to ethical issues. These issues include questions like whether manipulating a person with dementia is ethically permissible if it promotes her best interest or how to engage with a person who is unwilling to recognize that she has dementia. To help people living with dementia and their carers manage ethical issues in dementia care, we developed the CARE intervention. This is an intervention focused on promoting the ethical self-efficacy of people living with dementia and carers, i.e., their confidence that they can manage ethical issues when they occur. The purpose of this paper is to explain and discuss how we have developed the CARE intervention to promote the ethical self-efficacy of people living with dementia, their family, and professional carers through a specific and, we believe, new use of literary texts. Methods The CARE intervention has been developed in two phases: First, we conducted a needs assessment of the occurrence of ethical issues in dementia care and the need for an intervention to support people living with dementia and their carers in managing such issues. Second, in a design phase, we developed the CARE intervention to meet identified needs. Results To address identified ethical issues in dementia care we designed the CARE intervention as a workshop format where people living with dementia and carers can meet, discuss literary texts, and deliberate on how to solve such issues. The workshop is structured by the following elements: An agenda of ethical issues, a collection of literary cases exemplifying ethical issues, a moderator with an understanding of dementia care, and an overview of the ethical principles relevant to the discussion of ethical issues. >This workshop concept is operationalized in three applications tailored to meet the specific ethical issues of each of the study´s three target groups: people living with dementia and family carers, professional and family carers, and professional carers. Conclusion We conclude the paper by stating that it is possible to develop an intervention that promotes the ethical self-efficacy of people living with dementia and family and professional carers.